2022
DOI: 10.3389/fnut.2022.982878
|View full text |Cite
|
Sign up to set email alerts
|

Effect of wheat bran dietary fiber on structural properties and hydrolysis behavior of gluten after synergistic fermentation of Lactobacillus plantarum and Saccharomyces cerevisiae

Abstract: The effect of synergistic fermentation of Lactobacillus plantarum and Saccharomyces cerevisiae on the structural properties and aggregation behavior of gluten containing different wheat bran dietary fiber (WBDF) levels (0, 3, 6, 9, and 12%) was investigated. The results showed that WBDF addition affected the aggregation behavior of gluten at the molecular level, while WBDF significantly induced depolymerization behaviors in large aggregated gluten proteins (Molecular weight > 130 kDa) under reducing con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…The growth of microorganisms declined after reaching an optimal point. Previous studies (Yunilas et al 2019;Wang et al 2022;Baena et al 2022) emphasized that interactions among substrates, incubation periods, and the types and quantities of enzymes influence the degradation of crude fibers. The fermentation rate significantly affects enzymes produced in the medium (Pongsetkul et al 2022).…”
Section: Proximate Composition Of Fermented Rain Tree Seed Mealmentioning
confidence: 99%
“…The growth of microorganisms declined after reaching an optimal point. Previous studies (Yunilas et al 2019;Wang et al 2022;Baena et al 2022) emphasized that interactions among substrates, incubation periods, and the types and quantities of enzymes influence the degradation of crude fibers. The fermentation rate significantly affects enzymes produced in the medium (Pongsetkul et al 2022).…”
Section: Proximate Composition Of Fermented Rain Tree Seed Mealmentioning
confidence: 99%
“…The starch content in wholegrain flour (ST; %) was determined using a Total Starch Assay Kit (K-TSTA, Megazyme, Irishtown, Ireland) as reported in [31]. The amylose (AM; %) and amylopectin (AP; %) percentages in ST were determined using a Megazyme Amylose/Amylopectin Assay Kit (Megazyme Ltd., Bray, Ireland) following the procedures indicated by the manufacturer [32]. Accordingly, the AM to AP ratio (AM:AP) was calculated.…”
Section: Analysis Of Kernel and Doughmentioning
confidence: 99%
“…Furthermore, compared with the fermentation treatment of a single strain, the mixed treatments of two or more strains showed a synergistic effect and overcame their original defects. The mixed fermentation of LAB and SC has been applied to the fermentation of gluten and steamed bread [ 11 , 12 , 13 ]. Si et al [ 14 ] showed that mixed Cochliobolus kusanoi and Aspergillus puulaauensis fermentation significantly increased tea residue SDF compared with single bacteria fermentation, and showed a looser structure, lower crystallinity, and higher adsorption capacity in water, oil, and cholesterol molecules.…”
Section: Introductionmentioning
confidence: 99%